Analisis Ekonomi Solar Water Heater (SWH) Pada Bangunan Gedung Studi Kasus : Hotel Dangau Kecamatan Sungai Raya Kabupaten Kubu Raya - Bakar, Abu (ELKHA: Jurnal Teknik Elektro, 2016)
Abstract– Based on NASA satellite observations of daily insolation in 2013 at the location of hotel Dangau latitude u = 0.0, latitude, longitude t = 109.3, an average of 5.0816 kWh / m² / day. The high profile solar insolation in this location compared to the national average of 4.80 kWh / m² / day. This suggests a potential source of solar energy as a source of thermal energy which can be used to produce hot water by using the tool Solar Water Heater (SWH) or PATS. By using the means already PATS utilizing renewable energy sources. This thesis examines the economic analysis in the installation of a solar water heater in buildings Dangau  hotel. The use Solar Water Heater  are commonly used for both residential dwelling, hospital, swimming pool, hotel. From the analysis of the economic feasibility of investment by using the method of calculation of Net Present Value (NPV), the result is greater than one, while the value of Discounted Payback Period (DPP) is smaller than the life of the investment for 20 years, and the Internal Rate of Return (IRR) more greater than the Minimum Attractive Rate of Return (MARR). Investment by comparing energy prices and tariffs PLN show satisfactory results, with rates of Rp.1.352 PLN / kWh (industrial tariffs B2 / TR) produces Discounted Payback Period (DPP) 12 years and 6 months. Assuming PLN rate increase every year 5%, then the value obtained during the DPP for 8 years and 11 months of the project's life for 20 years. These results indicate that investment in hotel Dangau Solar Water Heater  installation is feasible.   Keywords– SWH,  NPV,  DPP,  IRR, NASA, PLN rate.